The PEth Blood Test in the Security Environment: What it is; Why it is Important; and Interpretative Guidelines. Issue 6 (13th July 2018) - Ulwelling, William; Smith, Kim
Abstract: Testing for phosphatidylethanol (PEth) is a relatively new tool for detecting and grossly quantifying a person's use of alcohol in a variety of security, medical, and legal environments. The basic chemistry of PEth is explained with a particular focus on factors that make it highly suitable as a biomarker for alcohol use in such situations. This article meets the need for a literature review that synthesizes PEth laboratory findings and suggests updated guidelines for interpretation. Several ethanol biomarkers have been used for detection or monitoring alcohol use but have significant limitations. Based on this review, the authors propose three guidelines for evaluating PEth values: Light or no Consumption (<20 ng/mL), Significant Consumption (20–199 ng/mL), and Heavy Consumption (>200 ng/mL). These guidelines are important in employment and security environments, but also have applicability in such diverse activities as alcohol treatment programs, organ transplant decisions, and monitoring impaired medical professionals.